Including voices : respecting the experiences of people from marginalised communities - Rose, Richard; Shevlin, Michael; Forlin, Chris (International perspectives on inclusive education, 2024)
While much has been written about inclusive education systems, researchers have mainly focused upon policies and practices to encourage access and participation for children with disabilities or special educational needs. Yet it is evident that the population of individuals and in some cases whole communities who have been denied access to schooling is much wider and more complex. The relationships that exist between poverty, class, sexuality, caste, gender, and exclusion from education are visible in many countries; these factors interacting to perpetuate exclusion. Including Voices considers the challenges and successes surrounding the development of equitable education by presenting the experiences of individuals who have themselves been the subjects of marginalisation. Through the presentation of research and an examination of exclusionary conditions, and the ways in which these are being challenged, the editors and authors present an important debate focused upon human rights and practical application of inclusive practices. A unique feature of Including Voices is the discussion generated about how the voices of individuals from marginalised communities and those who support them have been obtained, analysed, and reported. The editors provide a framework for encouragement of the respectful use of voices to further the cause of research that is inclusive.